Civic Participation in a Hybrid Regime: Limited Pluralism in Policymaking and Delivery in Contemporary Russia. Issue 1 (6th June 2017) - Owen, Catherine; Bindman, Eleanor
Abstract : This article asks why the Russian government has developed new avenues for public participation in policymaking and delivery and assesses the extent to which these avenues introduce pluralism into these processes. Drawing on 50 interviews with individuals and citizens' groups involved in either public consultative bodies or socially oriented NGOs, the article demonstrates the government's desire to harness the knowledge and abilities of citizens and civic groups in place of state departments perceived to be bureaucratic and inefficient, while controlling and curtailing their participation. Arguing that these countervailing tendencies can be conceptualized as limited pluralism, a category elaborated by Juan Linz and Alfred Stepan, we show that citizens and civic groups are able to influence policy outcomes to varying extents using these mechanisms.